TAKING INTO ACCOUNT THE JOINT OPERATION OF PRECAST CONCRETE COATING DISKS AS PART OF SPAN BENDING METAL STRUCTURES (Collection of scientific works «Modern structures of metal and wood», 2024)
Traditional  methods  of  beam’s  structures  calculation  for  industrial  buildings' coatings provide their consideration separately from the frame structures, in particular, reinforced concrete  slabs,  without  taking  into  account  their  joint  work,  which  leads  to  a  significant  safety margin of structures. Today, there is a significant number of industrial buildings and structures that require  strengthening  and  reconstruction  in  Ukraine.  In  this  regard,  studies  of  the  actual  load-bearing capacity of single-storey industrial building frames are particular importance, both during reconstruction and new construction. Their results will significantly reduce costs and allow for more rational design of structures. At the same time, one of the most relevant areas is the study of the joint  operation  of  metal  load-bearing  structures  with  precast  concrete  structures  of  hard  discs coatings and slabs in their calculation. Moreover, in the Ukrainian national design standards, as well as in the educational and methodological literature, the calculation methods for taking into account the joint operation of such structures are not fully covered. The  purpose  of  study  is  to  assess  the  reduction  of  metal  consumption  for    steel    truss structure  in  its  bending  calculation,  taking  into  account  the  joint  operation  with  a  rigid  precast concrete slab disc. Method. As part of the study, It was calculated a flat roof truss from the paired corners of an one-storey  industrial  building  according  to  the  traditional  design  scheme  –  without  taking  into account the joint operation with the slab disc and taking into account the joint operation with the slabs by means of numerical modelling as part of a roof block using the finite element method. The modelling of the pavement fragment (block) was performed in LIRA FEM 2022 software.  The main results. It is performed a comparative analysis of the internal forces in steel truss elements and the total mass of the truss based on the selected cross-sections of its elements by two design models. The practical significance of the obtained results is to determine the economic effect by reducing the material consumption and the degree of unloading of steel trusses as part of the roofing block of a one-storey industrial building, taking into account their joint operation with hard discs of precast concrete slabs.